La place Jemaa el-Fna au « printemps marocain » - Mari Oiry-Varacca; Lionel Gauthier (EchoGéo)
This paper seeks to shed light on the attack on the 28th of April, 2011, against a café situated on the Jemaa el-Fna square, a prime location of tourism and Marrakech heritage. To understand the impact of this event it is necessary, on the one hand, to address the complexity of the place (its symbolics, its uses, its actors) and, on the other hand, to decipher the specific political context in which it happens (Moroccan Spring). The analysis allows the highlighting of three types of impacts: socioeconomic (lowering tourism), identity (worsening of tensions) and political (acceleration of reforms at the national level).